2007
DOI: 10.1271/bbb.60563
|View full text |Cite
|
Sign up to set email alerts
|

Okara, Soybean Residue, Prevents Obesity in a Diet-Induced Murine Obesity Model

Abstract: We examined the effect of okara on the prevention of obesity in mice. A modified AIN-76 diet with a high fat content (14.1% of crude fat) was used as a basal diet. Male ICR mice were fed ad libitum with the basal diet or a dried okara-supplemented basal diet (10, 20, or 40%) for 10 weeks. The okara intake dose-dependently suppressed the development of body weight and epididymal white adipose tissue (EWAT), and prevented an increase of plasma lipids, including total cholesterol, LDL cholesterol, and non-esterif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 36 publications
4
31
1
1
Order By: Relevance
“…Table 4 showed that moisture content ranged from 9.88 to 4.71 % where sample UFAC had the highest moisture content and sample UFOK had the lowest value. The moisture content of sample UFOK was 4.71 % which was lower than the results obtained by Matsumoto et al (2007) that was 8.9 %. This could be from the difference in processing (drying time).…”
Section: Proximate Composition Of the Flours Prepared From Acha And Fcontrasting
confidence: 72%
“…Table 4 showed that moisture content ranged from 9.88 to 4.71 % where sample UFAC had the highest moisture content and sample UFOK had the lowest value. The moisture content of sample UFOK was 4.71 % which was lower than the results obtained by Matsumoto et al (2007) that was 8.9 %. This could be from the difference in processing (drying time).…”
Section: Proximate Composition Of the Flours Prepared From Acha And Fcontrasting
confidence: 72%
“…13) Feeding efficiency was almost same in the two groups. Soy yogurt did not significantly affect food intake or body weight gain as compared with control diet.…”
Section: Resultsmentioning
confidence: 81%
“…33) Matsumoto et al have also reported up-regulation of the hepatic CYP7a1 gene due to ingestion of okara. 13) Since the expression of enzymes in cholesterol synthesis was down-regulated, in spite of up-regulation of CYP7a1, total bile acid excreted in the feces did not increase. Additionally, the expression of malic enzyme (ME) decreased.…”
Section: Dna Microarray Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…1) Evidence from human clinical and epidemiologic studies suggests that hyperlipidemia is one of the most important modifiable risk factors for coronary heart disease. 2,3) Its prevention and therapy should therefore be a worldwide priority, and numerous studies of agents beneficial in its treatment, including drugs, 4,5) natural products, 6,7) and foods, 8,9) have been reported. Spontaneously hyperlipidemic (SHL) mice, established by inbreeding of Japanese wild mice (Mus musculus molossinus), have high plasma cholesterol due to disruption of the apolipoprotein E (apoE) gene.…”
mentioning
confidence: 99%